SIKAP DOGMATIS WISATAWAN JEPANG TERHADAP PAKET TRIAL YOGA DI BAGUS JATI HEALTH & WELL BEING RETREAT - I Gusti Made Wendri; Ni Putu Somawati; Ni Made Sudarmini (Soshum: Jurnal Sosial dan Humaniora, 2013)
There are many factors causing the visitors to take decision of buying a product, the factors of which are ; internal factors, external factors, full factors, and inovations. As the result of this research, I, the researcher found that the internal factors have much influence on the desicion of the tourist in buying the Spa product of Bagus Jati Health and wellbeing Retreat. The primary datas are colleted by using structural as well as indepth interview to the visitor met accidently who were involving in the Trial Yoga Package, to the Yoga’s instructur,and the Spa therapist The datas then analized by descriptive qualitative, by which describing the datas found as it is,by constrasting the similarity and the difference relationship among.The other factors is also the inovation conduct by the management in creating the package, also has its important role in penetrating the culture of the jepanese, who are fanatic to their culture. The result of the datas have already processed will answer the purpose of this research.